2021
DOI: 10.1002/dta.3151
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolic studies of novel selective androgen receptor modulators and their use for doping control analysis

Abstract: Selective androgen receptor modulators were developed as a treatment of choice for diseases that are currently treated or symtomatically treated with steroidal androgens. The present study aimed to explore the metabolic pathways of four structurally unrelated SARMs, namely, PF‐06260414, TFM‐4AS‐1, BMS‐564929, and GSK 2881078, in terms of their potential toxicology or doping control analysis. Detected metabolism, mainly resulting from a single or multiple hydroxylations, methoxylation, demethylation, dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(65 reference statements)
2
7
0
Order By: Relevance
“…In vitro studies with equine liver microsomes also identified all of the above metabolites. In addition, the methoxylated metabolite M6 was detected, which agrees with the previously published report by Kowalczyk et al 37 However, this metabolite was not detected in the in vivo study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In vitro studies with equine liver microsomes also identified all of the above metabolites. In addition, the methoxylated metabolite M6 was detected, which agrees with the previously published report by Kowalczyk et al 37 However, this metabolite was not detected in the in vivo study.…”
Section: Resultssupporting
confidence: 92%
“…This article claims to identify four hydroxy‐metabolites based on their fragmentation patterns. GSK28811078 was studied in vitro for doping control analysis by Kowalczyk et al 37 Human liver subcellular fractions (microsomal and S9) were used in this study to investigate the metabolic pathway. Study results indicate that there are two major metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Pursuant to in vitro studies on SARMS in 2021, 49 the fact that in vivo data or systems imitating human physiology in a more advanced manner 107 remain critical was attested by an example of combined in vitro and in vivo studies as presented by Ameline et al, who investigated the metabolic fate of the phenylpropanolamine‐derived SARM S‐23 (Figure 1, 1 ) 108 . Employing human liver microsomes, hydroxylation (presumably at the molecule's B‐ring), glucuronidation, and dephenylation were observed as supported by LC–HRMS/MS analysis using a C‐18 analytical column (2.1 × 150 mm, 1.8 μm particle size) linked via negative ESI to a Q/TOF mass spectrometer.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Pursuant to in vitro studies on SARMS in 2021, 49 the fact that in vivo data or systems imitating human physiology in a more advanced manner 107 The intact S-23 was observed in post-administration urine samples until Day 28, alongside the hydroxylated metabolite also observed in the preceding in vitro experiments. Also, one bishydroxylated metabolite of S-23 was detected in vivo, whereas hair samples collected after the single-dose exposure to S-23 did not result in any finding at a method LOD of 0.1 pg/ml.…”
Section: Other Anabolic Agentsmentioning
confidence: 99%
“…Many proteomics studies are also being conducted to identify novel proteins and biological functions in plants [ 13 , 14 ] and on model organisms such as Tetrahymena thermophila to elucidate the involvement of many key proteins in the basis of biological processes [ 15 ]. There are several reports in the literature on the use of proteomic methods in antidoping tests [ 16 ], early medical diagnosis [ 17 , 18 , 19 , 20 ], and candidates for vaccine production [ 21 ].…”
Section: Introductionmentioning
confidence: 99%